Manajemen Risiko Keuangan Dalam Menunjang Stabilitas Usaha Mikro Kecil Dan Menengah (UMKM) Di Kabupaten Pringsewu - Juhainah, Juhainah (EL-EMIR Institute, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting regional economic growth, including in Pringsewu Regency. However, this sector is vulnerable to various financial risks such as income fluctuations, limited access to financing, and low financial literacy. This study aims to analyze the financial risk management practices implemented by MSME actors and their contribution to the stability of their businesses. The research approach used is descriptive qualitative with a case study method on several MSMEs in Pringsewu Regency. Data collection techniques were carried out through in-depth interviews, observation, and documentation. The results of the study show that Financial risk management plays a crucial role in maintaining the sustainability and resilience of Micro, Small, and Medium Enterprises (MSMEs), especially amidst fluctuating economic conditions. The main findings of this study indicate that the majority of MSMEs in Pringsewu face significant financial risks, with liquidity risk (70%) and credit risk (50%) being the primary challenges. However, only a small portion of MSME actors have implemented financial risk management strategies in a systematic manner. The adoption of practices such as routine cash flow recording, the use of emergency funds, and income diversification has been proven to enhance business stability by up to 85% and crisis resilience by up to 90% among MSMEs that actively apply risk management. Furthermore, MSMEs with strong financial literacy demonstrate greater access to formal financing and are better equipped to make rational financial decisions. The use of digital financial technologies has also begun to contribute positively to the efficiency of financial management and business transparency.